Experimental study of thermal and size effects on the uniaxial compression strength of Granite - J. Namdarian; M. Yazdani (مهندسی عمران شریف, 2022)
The exploration and extraction of hydrocarbon resources (oil and gas) as well as the geothermal energy at great depths of the rock layers have posed challenges for the stability of the drilling well wall at high temperatures. Also, the burial of nuclear waste leads to a great increase in temperature in the surrounding rocks and affects the properties of the rocks. In addition, drilling deep oil wells at a high temperature of the drilling area illustrates the importance of investigating the effect of heat on the rock strength. Therefore, understanding the effect of temperature changes on the physical and mechanical properties of rock is vital for designing rock structures and evaluating safety in rock engineering. In this study, uniaxial compressive strength of granite, a common type of rock in the Earth's crust, under different temperatures and in different sizes is investhgated. For this purpose cylindrical specimens with diameters of 28 mm, 54 mm, and 84 mm were prepared and tested at laboratory temperatures and temperatures of 100, 200, 400, and 600 ° C. The samples were subjected to compressive loading and heating simultaneously. The results of the tests showed that uniaxial compressive strength decreased with increasing the temperature. At temperatures below 400 ° C, water begins to evaporate and escape through the cracks at a relatively slow rate. This creates a high air pressure and intensifies the formation and expansion of the cracks and pores and increases the cracks. As temperature rises above 400 ° C, chemical changes occur in the rock, which may reflect the color change of the sample. The quartz phase transition results in an increase in microcracks due to different expansion between the quartz grains and other minerals, which is one of the reasons for the decrease in strength between 400 and 600 ° C. The reduction in strength at 600 ° C was obtained for 28 mm diameter, 47%, for 54 mm diameter was 53% and for 84 mm diameter was 56%. Also, at a constant temperature, the uniaxial compressive strength decreased as the diameter increases. These changes are observed at all sizes.